Viola ornata and Viola longibracteolata (Violaceae, subgen. Neoandinium), two rare, new rosulate species from southern Peru - Gonzáles, Paúl; Montesinos-Tubée, Daniel B.; Watson, John M.; Cano, Asunción; Trinidad, Huber; Navarro, Eduardo; Jans, Harry; Sheader, Martin; Ballard, Harvey E.; Flores, Ana R. (Phytotaxa, 2022)
Two high Andean taxa from South Peru, Viola ornata and Viola longibracteolata, are described and illustrated. During a series of ecotourism and botanical expeditions in the Moquegua and Arequipa regions, four populations of V. ornata and one population of V. longibracteolata were discovered. Both species are compared with morphologically similar species of subg. Neoandinium. Their resemblances and differences are discussed, including by means of a key. We have determined the potential IUCN status of both new species as Critically Endangered (CR).